2014
DOI: 10.1902/jop.2013.130260
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐Rich Plasma–Assisted Guided Bone Regeneration for Ridge Augmentation: A Randomized, Controlled Clinical Trial

Abstract: These clinical and histologic findings suggest that PRP enhanced bone regeneration and resulted in increased horizontal bone gain and percentage vital bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 20 publications
3
84
1
1
Order By: Relevance
“…There is a general clinical impression that the ridge augmentation results are compromised in the case of early membrane exposures [32, 33]. In this case-controlled study, which was based on a patient subset from our previous randomized clinical trial, the clinical effect of exposure of a bioresorbable matrix membrane was evaluated [27]. Based on clinical ridge width dimension measurements, a mean ridge width gain of 1.4 and 2.6 mm were calculated for the test and the control group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There is a general clinical impression that the ridge augmentation results are compromised in the case of early membrane exposures [32, 33]. In this case-controlled study, which was based on a patient subset from our previous randomized clinical trial, the clinical effect of exposure of a bioresorbable matrix membrane was evaluated [27]. Based on clinical ridge width dimension measurements, a mean ridge width gain of 1.4 and 2.6 mm were calculated for the test and the control group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, the optimal dosage and carriers for PDGF are still to be determined and further animal and human studies are necessary before clinical application. A new approach to bone augmentation is separation of platelet-rich plasma (PRP) from patient blood to be added to the graft material [362,363,364,365]. Initial results showed more and denser bone compared to autografts used alone for bone augmentation procedures [362].…”
Section: Developments and The Future Of Bone Augmentationmentioning
confidence: 99%
“…In this case, we decided to mix WTA with platelet concentrates as they have shown to act as the source of growth factors promoting angiogenesis around bone graft and newly formed bone. [1819] This has been supported by findings of Gomes et al who evaluated the effects of homogenous DDM (HDDM) slices and platelet-rich plasma (PRP) in the treatment of surgical defects created in diabetic rabbits using GBR technique. Their histological analysis revealed that HDDM promoted not only increased bone formation but also superior bony microstructure owing to graft's osteoinductive and osteoconductive activities, while PRP stimulated angiogenesis and red bone marrow formation.…”
Section: Discussionmentioning
confidence: 74%